INTERROGATING THE PURPOSE OF SECONDARY EDUCATION IN ETHIOPIA: RHETORIC AND REALITY - Negesso, Lemessa Abdi; Kenea, Ambissa (Sanata Dharma University Yogyakarta, 2022)
The study examined the prevailing purpose of secondary education. Interview, questionnaire and observation are the tools used to collect data from curriculum experts, secondary school leaders, teachers, students and classrooms. Independent t-test was used to analyze quantitative data. Qualitative data obtained through interview, observation, and document analysis were analyzed using narrative description. Though the results from analysis of the Education Policy and related documents indicated the purpose of secondary education is to prepare students both for the world of work and for further education, key stakeholders perceived preparation for national examinations and higher education as the major intent of secondary education. It was found that experts, educators and students had no adequate understanding about the half part mission of secondary education, preparation for work. It was also found that the curriculum wasn’t designed to prepare students for work and teacher centered approach was the dominant pedagogical strategy employed in the schools. As a result, it is concluded that the prevailing purpose of secondary education is to prepare students for examination and higher education. It was suggested to enhance key stakeholders understanding about the entire purpose of secondary education and to revise the curriculum in use and pedagogical practices of the schools.